The Murine CD137/CD137 Ligand Signalosome: A Signal Platform Generating Signal Complexity - Choi, Beom K.; Lee, Hyeon-Woo (Frontiers in Immunology, 2020)
CD137, a member of the TNFR family, is a costimulatory receptor, and CD137L, a member of the TNF family, is its ligand. Studies using CD137- and CD137L-deficient mice and antibodies against CD137 and CD137L have revealed the diverse and paradoxical effects of these two proteins in various cancers, autoimmunity, infections, and inflammation. Both their cellular diversity and their spatiotemporal expression patterns indicate that they mediate complex immune responses. This intricacy is further enhanced by the bidirectional signal transduction events that occur when these two proteins interact in various types of immune cells. Here, we review the biology of murine CD137/CD137L, particularly, the complexity of their proximal signaling pathways, and speculate on their roles in immune responses.